Pengembangan Usaha Kerupuk Ibu Hamidah di Dusun Lekong Dendek Desa Dasan Tereng Kecamatan Narmada, Kabupaten Lombok Barat - Baiq Ertin Helmida; Baiq Kisnawati; Lalu Mimbar; Satriawan; Faizatul Fajariah; Gina Septiani Putri; Aliya Azimatu Zahra; Baiq Deria Ayuning Fatika (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
This community service activity was conducted in Lekong Dendek Dusun, Dasan Tereng Desa, Narmada Kecamatan. The objectives of the activity were to: 1) enhance the motivation and entrepreneurial mindset of business owners, fostering a business development orientation; 2) improve business management capabilities through the implementation of better management practices; and 3) upgrade the quality of product packaging and labeling to increase value-added and market competitiveness. The implementation methods employed included outreach sessions, training, demonstrations, hands-on practice, and mentoring. Monitoring and evaluation were conducted to assess the extent to which the partners implemented the provided material. The program results were as follows: 1) an increase in motivation and entrepreneurial mindset among business owners; 2) improved business management skills, particularly regarding the importance of simple bookkeeping, separating business and personal finances, calculating production costs, and determining selling prices; 3) enhanced packaging and label quality, resulting in a more attractive and informative appearance for the *kerupuk* (cracker) products, along with clearer product identity; 4) the participatory approach combining outreach, training, and mentoring—proved effective in increasing partners' knowledge and skills while fostering behavioral changes in business management; and 5) the service activity provided tangible benefits to the partners, serving as an initial step toward professionalizing business management and strengthening the competitiveness of MSMEs in Dasan Tereng Desa.